2013
DOI: 10.1016/j.bbapap.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure-based exploration of the important role of Arg106 in the RNA-binding domain of human coronavirus OC43 nucleocapsid protein

Abstract: Human coronavirus OC43 (HCoV-OC43) is a causative agent of the common cold. The nucleocapsid (N) protein, which is a major structural protein of CoVs, binds to the viral RNA genome to form the virion core and results in the formation of the ribonucleoprotein (RNP) complex. We have solved the crystal structure of the N-terminal domain of HCoV-OC43 N protein (N-NTD) (residues 58 to 195) to a resolution of 2.0Å. The HCoV-OC43 N-NTD is a single domain protein composed of a five-stranded β-sheet core and a long ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 60 publications
1
69
0
Order By: Relevance
“…We determined the crystal structure of MERS-CoV N-NTD by molecular replacement (MR) using the structure of HCoV-OC43 N-NTD (PDB ID: 4J3K) as the search model. 24 The final structure was refined to R-factor and R-free values of 0.26 and 0.29, respectively, at a resolution of 2.6 Å (Table S1). Each asymmetric unit contained four N-NTD molecules assembled into two identical dimers with an overall RMSD of 0.28 Å between the dimers ( Figure S1A,B).…”
Section: ■ Resultsmentioning
confidence: 99%
“…We determined the crystal structure of MERS-CoV N-NTD by molecular replacement (MR) using the structure of HCoV-OC43 N-NTD (PDB ID: 4J3K) as the search model. 24 The final structure was refined to R-factor and R-free values of 0.26 and 0.29, respectively, at a resolution of 2.6 Å (Table S1). Each asymmetric unit contained four N-NTD molecules assembled into two identical dimers with an overall RMSD of 0.28 Å between the dimers ( Figure S1A,B).…”
Section: ■ Resultsmentioning
confidence: 99%
“…However, the nucleic acid interaction surface within SARS-CoV NTD was roughly delineated experimentally by monitoring nuclear magnetic resonance (NMR) chemical shift perturbation upon RNA titration (36). Abundant mutagenesis data from homologous NTDs corroborate the extent of the binding surface and highlight particular residues involved in the interaction (35)(36)(37)(38)(39). The crystal structure of the NL63 NTD revealed a network of sulfate ions, mostly coordinated by positively charged residues.…”
Section: Resultsmentioning
confidence: 99%
“…The results described above are consistent with prior mutagenesis data obtained for beta-and gammacoronavirus NTDs. In IBV, residues equivalent to positions 61, 63, and 77 in NL63 were experimentally demonstrated to participate in the nucleic acid interaction (37), and the residue equivalent to position 61 is involved in nucleic acid binding by OC43 (38). Further, residues at positions equivalent to positions 59 and 75 (39), and 77 of NL63 (33), are important for nucleic acid binding by MHV.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the N terminus of the N protein provides a scaffold for RNA binding. Structural analysis revealed that the fold and the distribution of the secondary structures of the N-terminal domain of the N protein are essentially conserved across the various CoVs [41,55]. The core of the structure of CoV N-NTD adopts a unique five-stranded antiparallel b-sheet sandwiched between loops (or short 3 10 helix) with the topology of b4-b2-b3-b1-b5; and the whole structure presents a righthanded fist-shaped structure in which palm and finger are rich in basic residues and the flexible loops are organized around the bsheet core of the N-terminal domain ( Fig.…”
Section: A Concise Survey Of the Structural Features Of Coronavirus Nmentioning
confidence: 99%
“…All CoV N-NTDs possess positively charged amino acids on or near the protruding loop; however, in the SARS-CoV, mouse hepatitis virus (MHV) and avian infectious bronchitis virus (IBV) N-NTDs the protruding segment comprises a b-hairpin, whereas a flexible loop predominates in the HCoV-OC43 N-NTD. Based on the surface charge distribution, the protruding loop of the CoV N-NTD containing several positively charged residues, for example, Arg 106, Arg 107 and Arg 117 in HCoV-OC43, were identified to provide a site for binding of the phosphate backbone of RNA through electrostatic interactions [55]. In the central core of MHV N-NTDs, there are two crucial conserved Tyr residues, Tyr 127 and Tyr 129, that are involved in RNA binding and mutations of these residues to alanine can lead to loss of virus replication [56].…”
Section: A Concise Survey Of the Structural Features Of Coronavirus Nmentioning
confidence: 99%